Tracing the Networks of Past Societies in Palaeoenvironmental Research. (4th March 2020) - Hall, Tegan; Penny, Dan
Abstract: Historical societies reshaped their environment in various ways; by clearing forest, cultivating crops, mining, and modifying waterways. Evidence of these activities persists in palaeoenvironmental archives, which represent comprehensive histories of human activity in a landscape. Analysis of settlement networks across landscapes is another common approach to investigating how past societies operated, but these analyses rarely incorporate palaeoenvironmental data. Here, we combine these two data sources to examine past socio‐political relationships in a society that experienced disruption and transformation. Applying network analysis, and using settlement histories built from palaeoenvironmental proxies for occupation and land use, this paper reconstructs population dynamics at several key nodes (cities) within the Khmer kingdom of Southeast Asia, before and after the climate stress and political upheaval of the 14th–15th centuries ce . Our results reveal how the Khmer city network transformed across space and the nature of the relationships that existed within the network prior to its disruption.